Dealing with firestorms : brand strategies to manage negative word of mouth during social media crisis - Jaworski, Madlen Nicol (2020)
The growth of the Internet and social media platforms is changing the way how individuals communicate with each other. Through the fast communication, companies are facing negative word-of-mouth (NWOM) through social media channels. Therefore, it is of high importance to control and manage the spread of negative electronic word-of-mouth (eNWOM) and shouldn’t be underestimated by brands. This dissertation explores the differences between four online response strategies, aimed at managing NWOM during a social media crisis. Effects are analyzed over brand attitude and consumers intention to pass on NWOM. An in-between experimental study design was implemented. It aimed to analyze how participants´ brand attitude (BA) and intention to pass on NWOM changed, after being randomly exposed to one of the four response strategies. The main conclusion obtained shows, that all of the strategy combinations tested, had statistically significant differences among each other. Therefore, they were not equal within their effectiveness on the construct of BA and their intention to pass on NWOM. Thus, all hypotheses of this dissertation were accepted. The “mortification” and “delay and reducing offensiveness” strategy result to be the most effective strategies managing online firestorms. The “no action” strategy results to be the less effective strategy in managing firestorm situations. By exploring the field of electronic NWOM brands lack of preparation of how to respond to online firestorms was recognized. Which is why this dissertation will add not only academic but also managerial value within this field of research.